Pain physicians' perspectives on chronic pain management during COVID-19 pandemic: An online survey - Samarjit Dey; Shovan Kumar Rath; Pankaj Surange; Rajendra Sahoo; Gaurav Sharma; Priyanka Dev (Indian Journal of Pain, 2020)
Background: The ongoing COVID-19 pandemic has affected the current health care to the core. As a result, there is a shift of focus on health care to control the pandemic. The chronic pain patients, though at risk, are also the sufferers. The aim of this online survey was to evaluate the perspective of the pain physicians on chronic pain management during COVID-19 pandemic in India. Methods: The survey was conducted under the aegis of Indian society for study of pain. The questionnaire in the form of Google Forms was filled by pain physicians online after webinar. Results: In this survey, majority of the pain physicians (71.12%) reported that they are practicing pain even during COVID pandemic but with precautions. Around 65.77% of the pain physicians were using telemedicine for consultation. A prior COVID test for interventional procedures was opted by 85.56% of pain physicians. Total 89.30% feel that personal protective equipment is necessary for doing pain interventions. Meanwhile, during the pandemic, 97.32% of the pain physicians are attending webinars to keep themselves updated. Conclusion: This survey of pain physicians' perspectives on impact of COVID-19 shows that chronic pain practice was greatly affected. Although webinars are a modality to keep the pain physicians updated, telemedicine has taken its stride forward to prove its major role during this pandemic for consultation. The personal protection is the new must-have among pain physicians in clinics and hospitals during and after pandemic.